1993
DOI: 10.1002/1097-0142(19930715)72:2<491::aid-cncr2820720227>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Elevated prostaglandin E2 production by monocytes is responsible for the depressed levels of natural killer and lymphokine-activated killer cell function in patients with breast cancer

Abstract: Background. Human natural killer (NK) cells mediate spontaneous cytotoxicity against tumor cells and represent the main precursors of lymphokine‐activated killer (LAK) cell activity. A comparison of some aspects of NK and LAK cell activity was undertaken in 85 preoperative patients with breast cancer and 75 healthy donors. Methods. NK cell activity (tested in 18‐hour cultures of effector peripheral blood mononuclear cells [PBMC] with K562 or MOLT‐4 tumor target cells) was significantly diminished in these pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0
4

Year Published

1994
1994
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(52 citation statements)
references
References 29 publications
3
44
0
4
Order By: Relevance
“…Prostaglandins were able to make macrophages and/or lymphocytes less sensitive to various stimuli (Pelus and Strausser, 1977;Schultz et al, 1978). Moreover, prostaglandin E 2 suppressed NK cells and lymphokine-activated killer (LAK) cells (Ohnishi et al, 1991;Roth and Golub, 1993;Baxevanis et al, 1993). The present studies showed that hepatic PGF 2R and PGE 2 concentrations were significantly increased in FB 1 -induced promotion of rat hepatocarcinogenesis (Tables 3 and 4), and in the female rats fed purified FB 1 , liver-associated antitumor response was decreased (Figure 1).…”
Section: Discussionmentioning
confidence: 50%
“…Prostaglandins were able to make macrophages and/or lymphocytes less sensitive to various stimuli (Pelus and Strausser, 1977;Schultz et al, 1978). Moreover, prostaglandin E 2 suppressed NK cells and lymphokine-activated killer (LAK) cells (Ohnishi et al, 1991;Roth and Golub, 1993;Baxevanis et al, 1993). The present studies showed that hepatic PGF 2R and PGE 2 concentrations were significantly increased in FB 1 -induced promotion of rat hepatocarcinogenesis (Tables 3 and 4), and in the female rats fed purified FB 1 , liver-associated antitumor response was decreased (Figure 1).…”
Section: Discussionmentioning
confidence: 50%
“…8 -10 A large body of evidence has shown PGs to have immune suppressive roles in cancer indicating host-related mechanisms responsible for tumor progression. 15,17,25,28 However, studies that investigated the direct role of PGs in tumorrelated mechanisms, i.e., tumor cell functions that are required for tumor progression, have been limited. 29 -31 The present study in our murine mammary tumor model revealed that tumor-derived PGs owing to COX-2 expression by tumor cells stimulated their migration and invasiveness as well as tumorinduced angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…44,47,48 PGE 2 inhibits T cell activation, suppresses NK cell activity, downregulates HLA class II expression and induces upregulation of FoxP3 and production of IL-10 in non-T reg cells, steering immune cell composition towards a T reg phenotype. [49][50][51] TGF- inhibits T cell proliferation, activation and the function of cytotoxic molecules like perforin or granzymes. 51 In addition, TGF- impedes DC maturation and antigen presentation, working synergistically with IL-10 in preventing T cell activation and IL-2-induced proliferation.…”
Section: Tumor Evasion and Immunosuppressionmentioning
confidence: 99%